2006
DOI: 10.1143/jjap.45.8348
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Coating Using DC Plasma Jet

Abstract: Hydroxyapatite (HAP)-coated implants on metallic substrates have been used as biomaterials. The problem is that the HAP coating on metallic substrates is easily exfoliated at the boundary between HAP and metallic, e.g., titanium (Ti) substrates. Therefore, a Ti-HAP functionally graded coating (FGC) is considered to improve the adhesion of Ti-HAP coatings. In this paper, Ti-HAP FGC is tested using a well-controlled DC plasma jet and discussed. It is confirmed that Ti-HAP FGC films with good adhesion within thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Therefore, feeding rate of HAP powders in the middle coat becomes higher and process time of HAP coating is longer than one in the previous result [8].…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Therefore, feeding rate of HAP powders in the middle coat becomes higher and process time of HAP coating is longer than one in the previous result [8].…”
Section: Resultsmentioning
confidence: 69%
“…We have reported that adhesion strength of prepared films is increased with increasing W j [8]. However, HAP is decomposed when W j is high.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations